2005
DOI: 10.1007/s00424-005-1448-9
|View full text |Cite
|
Sign up to set email alerts
|

Cation channel activity of mucolipin-1: the effect of calcium

Abstract: Mucolipidosis type IV (MLIV) is a rare, neurogenetic disorder characterized by developmental abnormalities of the brain, and impaired neurological, ophthalmological, and gastric function. Considered a lysosomal disease, MLIV is characterized by the accumulation of large vacuoles in various cell types. Recent evidence indicates that MLIV is caused by mutations in MCOLN1, the gene that encodes mucolipin-1 (ML1), a 65-kDa protein showing sequence homology and topological similarities with polycystin-2 and other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…Similar to the nonselective cation channel properties of TRP-ML1, pharmacological evidence demonstrated that NAADP-sensitive Ca 2ϩ release channel could also be blocked by L-type calcium channel inhibitors (diltiazem and dihydropyridines) and potassium channel blockers, including tetrahexylammonium (16). Although some recent studies reported different characteristics of TRP-ML1 channels in different cell lines or gene-transfected oocytes (13,(17)(18)(19), to our knowledge there has been no study that has characterized this TRP-ML1 channel in the lysosomes of native cells.…”
Section: Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp) Is Capmentioning
confidence: 91%
“…Similar to the nonselective cation channel properties of TRP-ML1, pharmacological evidence demonstrated that NAADP-sensitive Ca 2ϩ release channel could also be blocked by L-type calcium channel inhibitors (diltiazem and dihydropyridines) and potassium channel blockers, including tetrahexylammonium (16). Although some recent studies reported different characteristics of TRP-ML1 channels in different cell lines or gene-transfected oocytes (13,(17)(18)(19), to our knowledge there has been no study that has characterized this TRP-ML1 channel in the lysosomes of native cells.…”
Section: Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp) Is Capmentioning
confidence: 91%
“…Palmitoylation and phosphorylation at the carboxyl-terminal tail modulate trafficking and channel activity, respectively (16,17), although cleavage at the first luminal loop inactivates the protein (18). The selectivity of the MCOLN1 channel remains controversial, as different studies have suggested that the channel is permeable to Ca 2ϩ (19), K ϩ , Ca 2ϩ , and Na ϩ (20), H ϩ (21), and Fe 2ϩ (22). The accumulation of enlarged vacuolar structures observed in MLIV patients led to the suggestion that MCOLN1 may be involved in the regulation of the biogenesis of lysosomes, specifically in the reformation of lysosomes from endosome-lysosome hybrid organelles (23).…”
mentioning
confidence: 99%
“…The permeability of the MCOLN1 channel is still not well understood. However, most of the studies regarding this subject propose that MCOLN1 is a Ca 2ϩ -permeable channel, and the activity is regulated by changes in Ca 2ϩ concentration on either the cytosolic or luminal face of the membrane, thus indicating that Ca 2ϩ is an important modulator of MCOLN1 function (20,34). Furthermore, when a proline substitution was introduced into MCOLN1 to resemble the form of MCOLN3 known to cause the varitint-waddler (Va) mouse phenotype (TRPML1V432P), the resulting channel activity was inwardly rectifying, Ca 2ϩ -selective, proton-impermeable, and activated by low pH, further supporting a role for MCOLN1 as a Ca 2ϩ channel that drives membrane fusion events within the endosomal pathway (35,36).…”
mentioning
confidence: 99%
“…TRPML family: The TRPML family (see Qian and Noben-Trauth, 2005;Cantiello et al, 2005;Zeevi et al, 2007) consists of three mammalian members (TRPML1-3). TRPML channels are probably restricted to intracellular vesicles and mutations in the gene (MCOLN1) encoding TRPML1 (mucolipin-1) are the cause of the neurodegenerative disorder mucolipidosis type IV (MLIV) in man.…”
Section: Transient Receptor Potential (Trp) Cationmentioning
confidence: 99%